Inducing resistance of spanish cedar Cedrela odorata L. and mahogany swietenia macrophylla King against y Hypsipyla grandella (Zeller) by grafting - Pérez Flores, Julián (2006)
Tesis (Ph.D.) -- CATIE, Escuela de Posgrado, Turrialba (Costa Rica), University Idaho, 2006